Role of metadata in county governance performance: A case of county governmentsin Kenya - Neyole Misiko Jacob; Muchelule Yusuf; Carolyn Mwasaa Mbinya (The International Journal of Management Science and Information Technology (IJMSIT), 2017)
This document gives information on the adoption of metadata in the management of various units within the county. It brings to the fore the various categories of metadata that can be utilized to enable the counties visualize their objective. Metadata can be described as data about data it therefore details when, where and by whom a particular set of data was collected. It is therefore essential for understanding information stored in data warehouses. Many organizations since the advent of database technology, data warehousing and even recently cloud computing have been storing large volumes of data and information. Little of this data has been essential to this organizations whereas much percentage of the data has not been mined for utilization at all.
Keywords: 650; Metadata; County government; data; users